2011
DOI: 10.1111/j.1365-2133.2011.10234.x
|View full text |Cite
|
Sign up to set email alerts
|

Noncultured extracted hair follicle outer root sheath cell suspension for transplantation in vitiligo

Abstract: Extracted hair follicular ORS cell suspension can be a useful simplified transplantation method for vitiligo. The transplantation procedure should be reserved for patients with vitiligo stable for at least 1 year. A larger study is needed for further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 17 publications
5
111
0
1
Order By: Relevance
“…Based on the studies conducted in epidermal cell suspension, the authors had speculated the cell requirement to be less than 2000 cells/cm 2 . 4,14 In the present study, we found a significant correlation between the number of melanocytes transplanted and repigmentation rate at 24 week. When assessing the clinical and treatment characteristics associated with optimal pigmentation, we found that a statistically significant higher melanocytes were transplanted in patients achieving RP > 75% (Table 1).…”
Section: 13mentioning
confidence: 66%
“…Based on the studies conducted in epidermal cell suspension, the authors had speculated the cell requirement to be less than 2000 cells/cm 2 . 4,14 In the present study, we found a significant correlation between the number of melanocytes transplanted and repigmentation rate at 24 week. When assessing the clinical and treatment characteristics associated with optimal pigmentation, we found that a statistically significant higher melanocytes were transplanted in patients achieving RP > 75% (Table 1).…”
Section: 13mentioning
confidence: 66%
“…In the latest development, EHFORSCS, which is an enriched source of follicular inactive melanocyte (melanocyte stem cells), seems to be a good addition to the prevailing cell-based therapies for vitiligo. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Mohanty et al . [5] have modified the method of obtaining the follicular tissue by the FU extraction (FUE) method. They used autologous EHFORSCS for transplantation in vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Adult' stem cells include haematopoietic stem cells [40] , bone marrow stromal (mesenchymal) stem cells [41] , neural stem cells [42] dermal and hair follicular (keratinocyte and melanocyte) stem cells [43][44][45][46] , fetal cord blood stem cells [47] and several others [48] . Like Embryonic stem cells, they are capable of self-renewal throughout the organism's life, and also capable of differentiating into different mature cell types.…”
Section: Adult Stem Cellsmentioning
confidence: 99%